2017
DOI: 10.5812/ircmj.55579
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Manual Passive Muscle Shortening and Positional Release Therapy on Latent Myofascial Trigger Points of the Upper Trapezius: A Double-Blind Randomized Clinical Trial

Abstract: Background: Positional release therapy (PRT) has been suggested as an effective treatment for myofascial trigger points (MTrPs). Considering the mechanism of PRT, a new modified technique, known as Manual Passive Muscle Shortening (MPMS), is introduced for the treatment of MTrPs. Objectives: To compare the effects of MPMS and PRT on the sensitivity of latent MTrPs in the upper trapezius and determine the active cervical lateral flexion range. Methods: In this double-blind randomized controlled trial, 30 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For group (A), there was a significant difference in the paired t-test between pre and post treatment pain level as P-value was (0.0001). For group (B), there was a significant difference in the paired t-test between pre and post treatment pain level as P-value was (0.0001) as shown in table (4).…”
Section: Group (B)mentioning
confidence: 89%
See 1 more Smart Citation
“…For group (A), there was a significant difference in the paired t-test between pre and post treatment pain level as P-value was (0.0001). For group (B), there was a significant difference in the paired t-test between pre and post treatment pain level as P-value was (0.0001) as shown in table (4).…”
Section: Group (B)mentioning
confidence: 89%
“…Myofascial pain syndrome (MPS) of the trapezius is considered one of the main causes of neck pain and characterized by deep, intense pain of the skeletal muscles and their fascia and by the presence of one or more myofascial trigger points (MTrPs) , Although MTrPs can be formed in any muscle or muscle group, previous studies concluded that the upper trapezius muscle (UT) is the most commonly affected muscle (3,4). The motor innervation of the trapezius muscle is the accessory nerve.…”
Section: Introductionmentioning
confidence: 99%
“…KT method was developed from 1973 to 1979 by Dr. Kenzo Kase, in an intension to provide support for musculoskeletal structure without over immobilization and the side effect from it 15 . Kinesio tape is made from a thin elastic adhesive material that can be stretched from 120-140% creating a dynamic flexible tape 16 .…”
Section: Kinesio Taping (Kt)mentioning
confidence: 99%
“…Kinesio tape is made from a thin elastic adhesive material that can be stretched from 120-140% creating a dynamic flexible tape 16 . The tape without medicinal properties is water resistant and can remain on skin for 3 to 5 days 15 . It is found that KT increases the ROM, reduce swelling, inflammation, muscle tone, and can be used in muscle spasm, cramps prevention and speedy recovery of overloaded muscle 17 .…”
Section: Kinesio Taping (Kt)mentioning
confidence: 99%
See 1 more Smart Citation